Impact of COVID-19’s Pandemic on the Economy of Indonesia - Susilawati, Susilawati; Falefi, Reinpal; Purwoko, Agus (Budapest International Research and Critics University, 2020)
COVID-19 is a global health problem including in Indonesia. The increased case of COVID-19 proved to have quite a significant impact on the economy globally which may have affected stability in Indonesia. This method of collecting data is a method of study literature with secondary data types. Data is taken from the Internet with respect to the validity of information such as government official information, official online sites and processed results of valid data. After obtaining the existing reference, a sorting of information that is appropriate to the topic of discussion. Data analysis is presented in graphical form and comes with a descriptive narrative. Based on the research, the impact of COVID-19 pandemic affects the economy in Indonesia. The affected sectors during the COVID-19 pandemic are transportation, tourism, trade, health and other sectors, but the economic sector most affected by COVID-19 is the household sector. Optimizing the potential in the country, the decline of BI-7 Day Reverse Repo Rate (BI7DRR), the interest rate of Deposit facility, and Lending facility interest rate, monitoring of global and domestic economic development conducted by Indonesia was assessed precisely so that inflation and stability remain in control.